PATH ANALYSIS OF THE INFLUENCE OF JOB CHARACTERISTICS, PERSONALITY, AND JOB SATISFACTION ON THE PERFORMANCE OF COMMUNITY HEALTH CENTER NURSES IN SOUTH TANGERANG CITY - Sunarto, Ading; Moeins, Anoesyirwan; Sunaryo, Widodo (Yayasan Education and Social Center, 2025)
This study aims to analyze strategies for improving the performance of community health center nurses in South Tangerang City by strengthening job characteristics, personality, and job satisfaction. The study used a quantitative approach with a survey method involving 141 nurses from seven subdistricts, including Serpong, North Serpong, Pondok Aren, Ciputat, East Ciputat, Pamulang, and Setu. Data analysis was performed using path analysis to test the direct and indirect effects between variables. The results showed that job characteristics, personality, and job satisfaction had a direct, positive, and significant effect on nurse performance. Job characteristics and personality also had a direct, positive, and significant effect on job satisfaction. Furthermore, job satisfaction was found to mediate the relationship between job characteristics and personality on performance, although the mediating effect was not stronger than the direct effect. These findings confirm that job satisfaction plays an important role as a mechanism in bridging individual and job factors with performance, although its effectiveness as a mediator is partial. Theoretically, this study expands the understanding of the causal relationship between variables in the context of primary health care. Practically, the research results can be used as a basis for Puskesmas management to design policies to improve nurse performance through strengthening job design, personality development, and strategies to increase job satisfaction.